Debugging the Writing Process: Lessons From a Comparison of Students' Coding and Writing Practices. - Hassenfeld, Ziva R.; Bers, Marina Umaschi (Reading Teacher)
Since the 1960s, a group of educators and researchers have championed the idea that learning coding and learning to read and write are, in some sense, part of the same skill set, but the grounds for asserting that similarity have continually shifted. Some have argued that as texts increasingly integrate digital components, expertise in coding will become a central part of reading in the 21st century. Others seem to use the word literacy simply to mean an important skill, without necessarily asserting a deeper similarity. In this study of novice writers and programmers in a second‐grade classroom, the authors explored a third hypothesis: that there is a fundamental relation between the activities involved in creating a written story and in creating a computer program. The findings of this research suggest that teachers can use a combination of coding and writing to reinforce students' acquisition of the writing process.